2005
DOI: 10.1111/j.1365-2486.2005.001061.x
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning sources of soil‐respired CO2 and their seasonal variation using a unique radiocarbon tracer

Abstract: Soil respiration is derived from heterotrophic (decomposition of soil organic matter) and autotrophic (root/rhizosphere respiration) sources, but there is considerable uncertainty about what factors control variations in their relative contributions in space and time. We took advantage of a unique whole-ecosystem radiocarbon label in a temperate forest to partition soil respiration into three sources: (1) recently photosynthesized carbon (C), which dominates root and rhizosphere respiration; (2) leaf litter de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 29 publications
1
96
0
Order By: Relevance
“…As Hashimoto 8 suggested that forest soils in Thailand responded to soil temperature by soil incubation experiments, a temperature parameter 4 also may improve the estimation of annual CO 2 efflux to some extent. Moreover, seasonal variation in CO 2 sources should be studied in future because respiration of soil microbes and that of plant roots respond differently to seasonal environment 2,18 . In conclusion, carbon dynamics in the soil under teak plantations in western Thailand were determined by the soil moisture regime, which is controlled by seasonal rainfall pattern and annual rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…As Hashimoto 8 suggested that forest soils in Thailand responded to soil temperature by soil incubation experiments, a temperature parameter 4 also may improve the estimation of annual CO 2 efflux to some extent. Moreover, seasonal variation in CO 2 sources should be studied in future because respiration of soil microbes and that of plant roots respond differently to seasonal environment 2,18 . In conclusion, carbon dynamics in the soil under teak plantations in western Thailand were determined by the soil moisture regime, which is controlled by seasonal rainfall pattern and annual rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…We have to bear in mind, however, that measured data at each individual site may be influenced by additional factors apart from the temperature response function, such as soil moisture conditions (Rodrigo et al, 1997;Cisneros-Dozal et al, 2006), litter chemistry (Berg and Laskowski, 2005b) and soil quality (Conant et al, 2008). Still, the regression analysis based on the compound data set shows that the default response equation of Lloyd-Taylor in LPJ-GUESS can still be used for further work.…”
Section: Fit Of the Functionsmentioning
confidence: 99%
“…It is often conceptualised as several distinct pools with increasing residence times (Knorr et al, 2005;Kirschbaum, 2004;Eliasson et al, 2005) or as a continuous entity with gradually changing decay rates (Ågren and Bosatta, 1987;Bosatta andÅgren, 1999). Decomposition of SOM is highly complex, as it is driven by a combination of factors such as temperature (Berg and Laskowski, 2005a), moisture conditions (Cisneros-Dozal et al, 2006) and its chemical quality (Berg and Laskowski, 2005b;Weedon et al, 2009;Cornwell et al, 2008). Many biogeochemical models have been developed and applied to study the response of the carbon cycle to past, current and future changes in climate.…”
Section: Introductionmentioning
confidence: 99%
“…To date, this approach has been used to look at autotrophic and heterotrophic contributions over seasonal to interannual timescales in temperate (Cisneros-Dozal et al 2006;Gaudinski et al 2000), boreal (Czimczik et al 2006;Hahn et al 2006;Schuur and Trumbore 2006), and semi-arid ecosystems; and with manipulations of rain (Borken et al 2006) and snow ). In addition, 14 C partitioning may also be an effective approach to test more specific process-level hypotheses on shorter timescales, particularly when combined with automated soil respiration measurements .…”
Section: Isotope Approachesmentioning
confidence: 99%